PENYEBAB KECELAKAAN KERJA MENGGUNAKAN HUMAN FACTORS ANALYSIS AND CLASSIFICATION SYSTEM (HFACS) PROYEK PEMBANGUNAN RUMAH SAKIT UMUM KOTA SOLOK DI PT DETAIL MULTI KONTRUKSI - Dina Waldani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Construction work is the whole or part of the activities that include the construction, operation, maintenance, demolition, and rebuilding of a building. In June 2019 there were 4 work accidents in the Solok City General Hospital construction project and there were 4 levels of human error that could potentially cause the accident, namely unsafe acts, unsafe conditions, and unsafe supervision. unsafe supervision), and organizational influences (influences of an organization). The purpose of this study was to determine the frequency distribution of unsafe act, precondition for unsafe act, unsafe supervision and influence of an organization using the Human factors analysis and classification system (HFACS) model approach. The design of this study was cross sectional using a quantitative approach. The total sample studied was 40 people. The results showed that 37% (15 people) were in the unsafe category at work at the unsafe act level, 22% (9 people) were in the poor category at the unsafe condition level, 33 people (82%) had a good perception of unsafe supervision. , and the respondents who have a good perception of the influence of an organization are 85% (34 people). It is suggested that the company should place workers according to their abilities, add safety signs in the construction area, increase work supervision during overtime hours, procure PPE according to standards, and conduct OSH training according to project needs.